PENDIDIKAN KARAKTER BERBASIS GENDER - Ikhsan, Moh Hayatul (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
Gender-based character education is an important topic in the field of education, as it addresses moral and ethical values shaped by gender roles. This study aims to explore how character education can be adapted to meet the different gender needs and how its implementation can impact students' development. The method used in this research is a qualitative approach, with data analysis through interviews and observations in educational settings. The results show that gender-based character education not only helps in the formation of students' morals but also strengthens awareness of gender equality. This indicates that a gender-sensitive approach in character education can influence students to have a more open and fair view of gender differences. This research provides a significant contribution to the development of inclusive and gender-sensitive character education policies.